Therapeutic Potential of Oxalis latifolia: Phytochemical Profiling and Green Synthesis of Functional Nanoparticles - J, Malavika; P, Athira; G, Gayathri; M, Slowmo; Krishnasamy, Thenmozhi (Sciences of Phytochemistry, 2026)
Plants are a highly diverse group of organisms that produce a wide range of biomolecules with distinct chemical compositions. Despite the advancements in contemporary therapies, medicinal herbs have been increasingly important in recent years. The genus Oxalis, belonging to the family Oxalidaceae, encompasses a diverse range of plants, many of which have been long prized for their therapeutic properties, spanning from contemporary pharmaceutical research to traditional herbal therapies. The present investigation comprehensively evaluated the phytochemical profile and in vitro antioxidant potential of Oxalis latifolia crude extracts. Among the solvent systems examined, the ethanolic leaf and stem extracts yielded the highest extractive yield and were particularly enriched in phenols, tannins, and flavonoids, correlating with promising antioxidant activity. The biosynthesised silver nanoparticles derived from the plant extract were systematically characterised using UV-visible spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction analysis, and Fourier transform infrared spectroscopy. Confirming their successful formation and crystallisation. Furthermore, the synthesised nanoparticles unveiled significant in vitro anti-inflammatory activity, highlighting the fundamental therapeutic potential of this species.